Multidecadal delay between deglaciation and formation of a proglacial lake sediment record. (15th October 2022) - Piret, Loic; Bertrand, Sebastien
Abstract: Basal ages obtained from proglacial lake sediments are often used to constrain deglaciation histories, based on the assumption that fine-grained stratigraphic records start forming immediately after glacier retreat. Here, we test this assumption by studying the onset of sedimentation in Calluqueo Lake, Chilean Patagonia, which progressively deglaciated between the 1940s and the end of the 20th century. Although the glacier-proximal basin has been ice-free for at least three decades, it does not yet contain a fine-grained stratigraphic record, despite the modern sedimentation rate of ∼3 cm yr −1 . By comparison, the distal basin contains a fine-grained stratigraphic record starting in 1997 ± 2 CE, i.e., 20–50 years after it was deglaciated. Based on these results, we show that several decades are required for ∼1 m of fine-grained sediments to accumulate between the coarse till material and sufficiently smoothen the uneven lake floor to start forming a fine-grained stratigraphic record. Although the exact timing depends on lake floor morphology and sediment accumulation rates, our results suggest that proglacial lake sediment records lack the first decades of sedimentation. This delay is mostly negligible when using radiocarbon ages from basal sediments to date glacier retreat since it falls within the range of radiocarbon uncertainties, though its importance increases throughout the Holocene. It is however significant for chronologies entirely based on varve-counting. Therefore, our results support the use of basal ages to establish deglaciation chronologies but they call for attention when using them to reconstruct Holocene ice retreat, especially with varve chronologies. Highlights: First evidence of a delay between deglaciation and fine-grained stratigraphic record. The fine-grained stratigraphic record starts 20–50 years after deglaciation. Basal ages lag deglaciation by several decades.